REGENERATION SYSTEM OF LETTUCE (LACTUCA SATIVA L.) THROUGH IN VITRO CULTURE - O. V. Romanova; A. V. Soldatenko; V. S. Romanov (Овощи России, 2019)
The article is devoted to the problem of obtaining regenerative plant varieties of lettuce (Lactuca sativa L.) Bouquet, Emerald, Chameleon (FSBSI Federal Scientific Vegetable Center). Salad culture is insensitive to in vitro conditions and requires the development of alternative regeneration conditions. Seeds were surface sterilized in 96% ethanol (30 s), then 15 minutes in 50% aqueous solution of "Whiteness" with the addition of Twin-20 (1 drop per 100 ml), washed three times in sterile distilled water. Then lettuce seeds were placed in Petri dishes on Gamborg B5 medium (2% sucrose, 3,0 g/l fitogeli). After 10 days, the obtained seedlings were cut, the leaf blades were cut into squares 1 cm in size and transferred to medium MS B5 (2% sucrose) with three variants of hormone concentrations: 0.1 mg/l NAA and 1 mg/l BAP, 1 mg/l NAA and 1 mg/l BAP, 1 mg/l NAA and 0.1 mg/l BAP. The formed shoots were rooted on MS medium (2% sucrose, 7,0 g/l agar). Cultivation was carried out on racks with fluorescent lamps at 25°C and a photoperiod of 14 hours, illumination of 2,5 thousand Lux. According to the results of studies, the concentration of hormones (0,1 mg/l NAA, 1 mg/l BAP) was selected, which allowed to obtain up to 10 shoots from one leaf explant. Moreover, the largest number of shoots was noted on leaf explants located closer to the veins of the sheet. The obtained data allowed to improve the system of regeneration of varieties of emerald lettuce, Bouquet and Chameleon.